Novel Interaction Solutions to Kadomtsev-Petviashvili Equation - 吕大昭 崔艳英 刘长河 张蒙 (Communications in theoretical physics, 2010)
In this paper, based on the forms and structures of Wronskian solutions to soliton equations, a Wronskian form expansion method is presented to find a new class of interaction solutions to the Kadomtsev-Petviashvili equation. One characteristic of the method is that Wronskian entries do not satisfy linear partial differential equation.